Early palliative care and quality of life of advanced cancer patients—a multicenter randomized clinical trial - Franciosi, Vittorio; Maglietta, Giuseppe; Esposti, Claudia Degli; Caruso, Giuseppe; Cavanna, Luigi; Bertè, Raffaella; Bacchini, Gianpaolo; Bocchi, Letizia; Piva, Erico; Monfredo, Michela; Scafuri, Valentina; Cesare, Pamela Di; et al. (Annals of Palliative Medicine; Vol 8, No 4 (September 27, 2019): Annals of Palliative Medicine, 2019)
Background: To compare quality of life (QoL) of patients receiving early palliative care (EPC) vs. standard oncologic care (SOC). Methods: Pragmatic, multicenter, randomized trial at five University and Community Hospital Cancer Centers in Northern Italy. Advanced non-small cell lung, gastric, pancreatic and biliary tract cancer patients diagnosed within the previous 8 weeks. In the EPC arm, visits were performed systematically by a dedicated physician/nurse palliative care (PC) team, who assessed physical and psychosocial symptoms, and enacted the necessary services. In the SOC arm, PC visits were only carried out if requested. The primary outcome was the difference in the change of QoL [Functional Assessment of Cancer Therapy-General measure (FACT-G)] from baseline to 12 weeks in the two groups. Results: From November 2014 to March 2016, 281 patients were enrolled (142 EPC, 139 SOC); 218 completed FACT-G at 12 weeks. Baseline demographic and clinical characteristics were similar for the two groups. Values of FACT-G at baseline and 12 weeks were 72.3 (SD 12.6) and 70.1 (SD 15.5) for patients enrolled in the EPC arm, vs. 71.7 (SD 14.7) and 69.6 (SD 15.5) for the SOC arm, but the change scores did not differ significantly between groups. In the multivariable analysis, adjusting for QoL at baseline, two potential prospective prognostic factors were statistically significant: lung cancer (P=0.03) and interaction of living without a partner and intervention arm (P=0.01). Dying within 6 months (P